Peran Orang Tua dalam Mendukung Perkembangan Bahasa Anak Usia Dini (4–5 Tahun) - Ainun Najib; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Language development is a crucial aspect of early childhood growth, particularly at the age of 4–5 years, which represents a critical period for communication skills development. This study aims to analyze the role of parents in supporting early childhood language development. The method used is a literature review by examining relevant journals and books related to children's language development and parental involvement. The findings indicate that active parental involvement through intensive interaction, two-way communication, play activities, and shared reading habits has a positive impact on children's vocabulary acquisition and speaking abilities. In contrast, a lack of stimulation and parental involvement may lead to delays in language development. Therefore, parents need to have adequate awareness and understanding in providing appropriate language stimulation according to the child’s developmental stage. This study recommends the importance of active parental involvement in creating a supportive environment to optimize children's language development